2008
DOI: 10.1016/j.ajo.2008.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Face-Down and Seated Position After Idiopathic Macular Hole Surgery: A Randomized Clinical Trial

Abstract: A face-down postoperative position is highly recommended in holes larger than 400 microm. The size of the idiopathic MH seems to be an important factor affecting outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
94
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(102 citation statements)
references
References 33 publications
4
94
1
3
Order By: Relevance
“…The results of this study are consistent with those of Guillaubey et al 17 in suggesting that post-operative face-down positioning can improve the likelihood of macular hole closure. The possible benefit of face-down positioning appears to be relevant to macular holes of greater than 400 mm in diameter.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The results of this study are consistent with those of Guillaubey et al 17 in suggesting that post-operative face-down positioning can improve the likelihood of macular hole closure. The possible benefit of face-down positioning appears to be relevant to macular holes of greater than 400 mm in diameter.…”
Section: Discussionsupporting
confidence: 83%
“…In our study, we observed an anatomical closure rate of 93.3% and a mean visual acuity gain of 0.23 logMAR unit in the posturing group, a result that is consistent with previously published data. 17,21 In the non-posturing group, in contrast, we found a MH closure rate of only 60% and a mean visual acuity gain of 0.05 logMAR unit. The non-posturing group may have a worse outcome because of increased risk of cataract.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…10 For holes > 400 µm, success rate has been found to be significantly higher with face-down posturing than sitting posture after surgery (95.1% versus 79.5%). 15 The low rates of hole closure in our study may be attributed to poor compliance with post-operative head posturing or large hole size.…”
Section: Discussionmentioning
confidence: 52%
“…In a large randomised trial of posturing for macular hole, patients who had combined surgery did not have a higher success rate than those who had vitrectomy alone. 16 One argument against combined surgery is that biometry may be less accurate in the presence of macular disease that reduces central vision. 23 In common with some other authors we found a slight myopic overcorrection, which might be explained by an anterior displacement of the capsular bag caused by the gas bubble.…”
Section: Discussionmentioning
confidence: 99%